A framework for sustainable evaluation of thermal energy storage in circular economy. (September 2021) - Abokersh, Mohamed Hany; Norouzi, Masoud; Boer, Dieter; Cabeza, Luisa F.; Casa, Gemma; Prieto, Cristina; Jiménez, Laureano; Vallès, Manel
Abstract: The circular economy can be promoted as a solution to support the sustainability market position of renewable energy systems. To design a circular and sustainable system, a structured approach is needed. The present study develops a methodology framework for sustainable circular system design (SCSD), aiming to assess thermal energy storage (TES) technologies from a sustainable perspective. To this end, a composite indicator, namely, environmental sustainability and circularity indicator ( E S C ) is provided. This indicator combines the environmental impacts of the TES system via the conduction of a life cycle assessment and its circulatory performance using the product-level material circularity indicator ( M C I ). The developed methodology is applied to a case study of high-temperature TES using molten salts as a part of a concentrated solar power plant. The SCSD embraces the analysis for the most relevant processes through proposing different ecological scenarios including, increasing the recycling rates (Modest Scenario), increasing the reuse rates (Medium Scenario), and a combination of both (Optimistic scenario). The circularity analysis showed that for the Modest, Medium and optimistic scenarios, the M C I moves from 20.6% for the current situation to 30.3%, 38.6%, and 46.4%, respectively. Accordingly, the optimistic scenario showed the most environmentally sustainable and circular scenario with E S C of 7.89%, whereas the Modest and Medium scenarios exhibited E S C s of 1.20% and 2.16%, respectively. A major obstacle for substantial improvement of the circulatory and E S C is the high share of unrecyclable molten salts in the system and therefore, any effort to improve the circulatory and the environmental benefits of this system can be reached by using more environmentally friendly alternative materials. The study concludes that the integration of reusing and recycling at the initial design should be sought in order to achieve a more environmentally sustainable and circular outcome. Graphical abstract: Image 1 Highlights: A sustainable circular system design framework is developed. A framework application is illustrated through molten salt thermal energy storage. Different scenarios for the EU 2030 waste management targets are analyzed. The reuse concept is the key factor to achieve circular economy designs. The circular economy concept can improve energy storage sustainability 30 times.